PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN TEAM GAMES TOURNAMENT KELAS V SDN 29 PONTIANAK KOTA - Mukromiyono, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â Abstract This study aimed to describe the learning outcome of students in the learning of Social Science by using Team Games Tournament in Class V State Elementary School 29 Pontianak Kota. The research method used is descriptive. Form of research is classroom action research. The sample was 31 students. Data were analyzed using direct observation. Data collectors are teacher observation sheet of learning ability in planning and implementing the learning process. This research was conducted three cycles, with the result; (1) The ability of teacher to prepare lesson plan first cycleÂ 2.80, 3.21 second cycle, and the third cycle 3.59 increased 0,41 in second cycle and 0.38 in third cycle. (2) The ability of teacher in implementing the learning first cycle of 2.80, 3.39 of second cycle and third cycle 3.64 increased 0.59 in second cycle and 0.25 in third cycle. (3) The result of study of students in the first cycle of 68.06, 76.45 in second cycle and the third cycle 87.10 increased by 8.39 in second cycle and 10.65 in third cycle. Team Games Tournament can improve learning outcome of social science in class V State Elementary School 29 Pontianak Kota. Â Keywords: Learning Outcomes, Social Science, Teams Games Tournament